2022
DOI: 10.1186/s12883-022-03018-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of stroke pre-hospital management in Lebanon from symptoms onset to hospital arrival and impact on patients’ status at discharge: a pilot study

Abstract: Background Hospital arrival time after acute ischemic stroke onset is the major factor limiting the eligibility of patients to receive intravenous thrombolysis. Shortening the prehospital delay is crucial to reducing morbidity and mortality for stroke patients. The study was conducted to investigate the factors that influence hospital arrival time after acute stroke onset in the Lebanese population and to assess the effect of the prehospital phase on patients’ prognosis at discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…16 Nonetheless, it was different in international studies, such as one held in Indonesia, where the median was 45 minutes, 29 and in another developed in Lebanon, where 32.9% underwent a CT scan in less than 20 minutes. 14 The time spent between the CT scan and the detection of ischemic stroke in the hinterland region was five times longer than in the capital city. In cases of HS, the hinterland took 1.4 times longer than the capital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 Nonetheless, it was different in international studies, such as one held in Indonesia, where the median was 45 minutes, 29 and in another developed in Lebanon, where 32.9% underwent a CT scan in less than 20 minutes. 14 The time spent between the CT scan and the detection of ischemic stroke in the hinterland region was five times longer than in the capital city. In cases of HS, the hinterland took 1.4 times longer than the capital.…”
Section: Discussionmentioning
confidence: 99%
“…28 On the other hand, a prospective crosssectional survey carried out in Lebanon showed that only 17.7% arrived late, taking more than 3 hours to the health care unit. 14 The discussions regarding time are delicate, because it was evident that investigation designs, materials and methods bring different interpretations for many of the comparisons shown, so that, when investigating time, it is perceived that the cutoff value used to exclude time data pre-hospital care of patients who arrive at the hospital with prolonged delays are different. With respect to the detection time (∆T Detection), it is worth highlighting that this referred to the time spent in the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the strategies used for the pre-hospital transport, networked stroke care, and real-time feedback systems are vital to be considered by the healthcare team ( Lossius and Lund, 2012 ; Kobayashi et al, 2018 ). The early recognition could be attained through various symptoms, including sudden weakness or numbness in the face, arm, or leg on one body side, immediate confusion, trouble speaking, difficult speech, trouble seeing in one or both eyes, dizziness, loss of balance or coordination, severe headache with no known cause ( Kamal et al, 2022 ; Ospel et al, 2022 ).…”
Section: The Importance Of the Healthcare Team In Treating Stroke Casesmentioning
confidence: 99%